Formation of Layer‐by‐Layer Assembled Cocatalyst Films of S2−‐Stabilized Ni3S4 Nanoparticles for Hydrogen Evolution Reaction. Issue 10 (23rd August 2017) - Kim, Sungwon; Nishino, Toshio; Saruyama, Masaki; Sakamoto, Masanori; Kobayashi, Hiroyuki; Akiyama, Seiji; Yamada, Taro; Domen, Kazunari; Teranishi, Toshiharu
Abstract: It remains challenging to develop alternatives, based on widely abundant elements, to highly active Pt catalysts for the hydrogen evolution reaction. Metal sulfide nanoparticles (NPs) are potential candidates for such catalysts because of their metallic features and intrinsic high surface area; however, their poor electrocatalytic activity, owing to the presence of surface ligands, is an obstacle to practical use. Here we report the selective synthesis of oleylamine (OAm)‐stabilized Ni3 S4 (Ni3 S4 /OAm) NPs. The insulating ligands were exchanged with S 2− and loaded on electrodes by a layer‐by‐layer (LbL) assembly method with metal cation linkers. The enhanced catalytic properties were confirmed by electrochemical measurements. A LbL assembled film with Ni 2+ as a linker (11 cycles) showed an overpotential of 555 mV@‐4 mA cm −2 at pH 6.8 and a stable current density for 12 h. In addition, when this LbL assembly method was applied to a CdS/Cu(In, Ga)Se2 photocatalyst electrode, the resulting photoelectrode showed an enhanced photocurrent compared with that of the Ni3 S4 /OAm NPs‐spin coated and bare photoelectrodes. These results indicate the versatility of LbL assembly for fabrication of ligand‐free NP electrocatalyst films. Abstract : S 2− ‐stabilized Ni3 S4 nanoparticles loaded on (photo)electrodes by a layer‐by‐layer assembly method with metal cation linkers showed high and stable catalytic properties in the hydrogen evolution reaction, indicating the versatility of layer‐by‐layer assembly for fabrication of electrocatalysts.